Une nouvelle subjectivité féminine en Iran - Khosrokhavar, Farhad (Esprit, 2023)
Les jeunes générations, notamment de femmes, rejettent un régime théocratique macabre au nom de la joie de vivre et de la liberté.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; com5170; cours; discipline; droits des femmes*; féminisme islamique; histoire et politique; iran; militance; patriarcat; premier cycle; périodes historiques; régions géographiques; résistance; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

Territoires en mouvement : femmes et danses de résistance en Arménie - Institut de recherches et d'études féministes
Et si danser devenait un acte de résistance, un territoire à soi quand tout disparaît ? Dans cet épisode, nous partons en Arménie avec Sona Pogossian, où la danse devient un pilier identitaire face à l’enclavement, à la perte de terres, et aux blessures de l’histoire. La danse, architecture vivante et mouvante, est un territoire immatériel que l’on porte en soi. Les femmes y incarnent un double pilier : celui de la mère et celui de la nation. Dans une société où la femme est le noyau de l’identité nationale, comme dans bien d’autres luttes pour l’autodétermination, la figure maternelle devient le symbole d’un « NOUS » collectif, profond et résistant. Biographie : Artiste de la scène, Sona a suivi de multiples formations en anthropologie et pratiques des arts scéniques, dont au sein du conservatoire de Lyon, de l’université d’État de Moscou d’Art et de Culture, de l’université Paris 8, entre autres. Son parcours pluriel l’amène aujourd’hui à réaliser un doctorat (thèse-création) à l’UQAM en études et pratiques des arts, où elle tente de mettre en lumière les corporalités des femmes en phénomène de guerre. Enregistré durant la Tournée des cégeps à l’automne 2024 (https://iref.uqam.ca/babillard/tournee-des-cegeps-foire-feministe-feministes-dans-la-cite/)par Juliette Chevet et Rajae Anys. Écrit et monté par Rajae Anys. Avec le soutien financier du CRSH.
Keywords: 2000 à aujourd'hui; 2020-2029; Arménie; arts; asie; danse; discipline; doits des femmes; foire féministe; guerre; maternité; militance; musique; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques